Role of Tyrosine Kinase Inhibition with Imatinib in an Encapsulating Peritoneal Sclerosis Rat Model. (May 2013) - Velioglu, Arzu; Tugtepe, Halil; Asicioglu, Ebru; Yilmaz, Neslihan; Filinte, Deniz; Arikan, Hakki; Koc, Mehmet; Tuglular, Serhan; Kaya, Handan; Ozener, Cetin
<x xml:space="preserve">Abstract</x> Background: Encapsulating peritoneal sclerosis (EPS) is characterized by neovascularization, increased inflammation, and interstitial fibrosis of the peritoneum. We investigated the effects of imatinib on the peritoneal membrane in an experimental EPS model. Methods: We separated 24 non-uremic Wistar rats into four groups: the control group which was injected with 2 mL isotonic saline intraperitoneally (IP) daily for 3 weeks, the CG group which was injected with chlorhexidine gluconate (CG) IP daily for 3 weeks, the resting group which was injected with CG IP between weeks 0–3 followed by a peritoneal rest period between weeks 3–6, and the CG + Imatinib mesylate group (CG + IMA) which received CG through weeks 0–3 followed by 50 mg/kg imatinib mesylate through weeks 3–6. At the end of the study, we performed a 1-h-peritoneal equilibration test and examined the peritoneal function and transforming growth factor-β1 (TGF-β1) in dialysate. Morphologic changes were evaluated by microscopy and immunohistochemistry. Results: An increased ultrafiltration, dialysate/plasma-creatinine-ratio, end-to-initial-dialysate-glucose-ratio, decreased active mesothelial cell ratio and inflammation, and a slightly decreased TGF-β1 of dialysate were found in the CG + IMA group compared to CG alone. Furthermore, the CG + IMA group had a lower concentration of active mesothelial cells than did the resting group. Ultrafiltration was improved in CG + IMA group compared to resting group, however, significant decrease in peritoneal thickness and inflammation were not found compared to those in resting group. Furthermore, there was no significant difference in fibrosis or TGF-β1-positivity on immunohistochemistry between the groups. Conclusions: Tyrosine kinase inhibition with imatinib may lead to a decrease in mesothelial cell activity and an increase in ultrafiltration. However, peritoneal fibrosis was unchanged by imatinib in EPS model.